Harringtonine Inhibits Herpes Simplex Virus Type 1 Infection by Reducing Herpes Virus Entry Mediator Expression - Liu, Ye; You, Qiao; Zhang, Fang; Chen, Deyan; Huang, Zhenping; Wu, Zhiwei (Frontiers in Microbiology, 2021)
Herpes simplex virus type 1 (HSV-1) infection induces various clinical disorders, such as herpes simplex encephalitis (HSE), herpes simplex keratitis (HSK) and genital herpes. In clinical intervention, acyclovir (ACV) is the major therapeutic drug used to suppress HSV-1; however, ACV-resistant strains have gradually increased. In the present study, harringtonine (HT) significantly inhibited infection of HSV-1 as well as two ACV-resistant strains including HSV-1 blue and HSV-1 153. Time-of-drug addition assay further revealed that HT mainly reduced the early stage of HSV-1 infection. We also demonstrated that HT mainly affected herpes virus entry mediator (HVEM) expression as shown by qPCR, Western Blot and Immunofluorescence. Collectively, HT showed antiviral activity against HSV-1 and ACV-resistant strains by targeting HVEM, and could be a promising therapeutic candidate for mitigating HSV-1-induced-pathogenesis.